PENGEMBANGAN KAPASITAS NELAYAN BUDIDAYA LOBSTER LAUT DALAM MENINGKATKAN KEMANDIRIAN BERWIRAUSAHA - Roslindah Daeng Siang; Sjamsu Alam Lawelle; Muis Balubi (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
Action research on marine lobster farmer group in the Rumba Rumba Village of the District Kolono performed using Participatory Action Learning System which is a method of community empowerment in regional development. This activity has a purpose, namely to: help create beraitan management cultivation techniques, marketing and bookkeeping better cultivation sea lobster. The results achieved in this activity include: 1) the application of methods of cultivation lobster sea water in a better way for business productivity thereby increasing the revenue of fishermen cultivating lobster 2) management of cultivation of lobster more effectively by arranging bookkeeping cultivation of lobster so that businesses more profitable, 3 ) institutional formation of fishermen. With some methods are introduced, able to contribute to the social, ie unlock insights and ways of thinking group of fishermen to manage their business and create jobs in the village and the ability of the fishermen cultivation in entrepreneurship on their own, which in turn can improve the economics of the household and help the development of the coastal village.Keywords: Institutional, Entrepreneurship, Fishermen, Sea Lobster